2020
DOI: 10.1055/s-0040-1721546
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation on Deep Caries Removal Method and Management Performed by Undergraduate Dental Students: A Malaysia Experience

Abstract: Objectives The aim of this study is to investigate the current knowledge and attitude of deep caries removal method among dental students in Malaysia. Materials and Methods A total of 303 students (n = 303) responded to the online questionnaire. The first part of questionnaire was to evaluate the demographic data of the respondents and focused on the technique and management approach used for deep caries lesion. The second part investigated the preferred treatment used for deep caries based on the designated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In assessing posterior restorations, the faculty members must first determine the desired learning outcome before selecting the assessment method, as the selection should be done according to the conventional outcomebased curriculum rather than the teacher-input-orientated traditional curriculum. The assessments conducted in the dental schools in Malaysia were made up of quizzes, mini examinations, clinical assessments and competency performance assessments designed in accordance with the four levels of Miller's Pyramid of clinical competence and the affective, psychomotor and affective domains in Bloom's Taxonomy of theoretical educational framework [29][30][31][32]. In this modern technological age, digital education implementation in posterior restoration teaching, such as e-learning and internet web-based education, is more desirable due to their practicality in facilitating the overall learning experience between students, lecturers, and faculty members.…”
Section: Discussionmentioning
confidence: 99%
“…In assessing posterior restorations, the faculty members must first determine the desired learning outcome before selecting the assessment method, as the selection should be done according to the conventional outcomebased curriculum rather than the teacher-input-orientated traditional curriculum. The assessments conducted in the dental schools in Malaysia were made up of quizzes, mini examinations, clinical assessments and competency performance assessments designed in accordance with the four levels of Miller's Pyramid of clinical competence and the affective, psychomotor and affective domains in Bloom's Taxonomy of theoretical educational framework [29][30][31][32]. In this modern technological age, digital education implementation in posterior restoration teaching, such as e-learning and internet web-based education, is more desirable due to their practicality in facilitating the overall learning experience between students, lecturers, and faculty members.…”
Section: Discussionmentioning
confidence: 99%
“…In response to changes to recommendations, there is clearly a need to improve VPT teaching to encourage guideline adoption, and consequently a need to develop appropriate ways to assess student performance in VPT. This was confirmed by studies with clinical scenarios that highlighted that the vast majority of the students selected pulp capping rather than partial pulpotomy in cases of carious pulp exposure (Gasqui et al, 2021; Othman et al, 2021). Furthermore, in a qualitative study, undergraduate students reported that pulp capping is technically easier and less stressful to carry out than partial pulpotomy, with the main problem of partial pulpotomy stemming from uncertainty regarding the ideal volume of pulp tissue to remove (Chevalier et al, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…These technologies enhance the micro-detailed visibility in the tiny operative field of dentistry. 66 , 67 Digital radiography has improved the quality of dental imaging and reduced radiation hazards. This may facilitate diagnosing proximal caries and close monitoring of post-treatment success.…”
Section: Clinical Outcomes Of Tunnel Restorations Using Different Res...mentioning
confidence: 99%